¿Abismo o armonía entre la imaginación y la razón? Una aproximación crítica a la Religionskritik Spinozas de Leo Strauss - Agustín, Volco; Guillermo , Sibilia (Foro Interno, 2009)
In his Religionskritik Spinozas Leo Strauss holds that Spinoza’s critique of religion expresses and bases itself “in the form of the crude antithesis between superstition, prejudice, ignorance, barbarism, benightedness on the one hand, and reason, freedom, culture, enlightenment on the other”. The critique of the religion appears then, according to Strauss, as “the critique…attempted by the radical Enlightenment”. Consequently there is in Spinoza’s theory a gap between the life of the wise, guided by reason, and that of the multitude, subject to passions, establishing a hierarchy between two clearly differentiated types of men. In this work we seek to examine this proposition focusing on the need to rethink not only the role of reason and imagination in Spinoza’s political speech, but particularly the relationship between them, which is fundamental for the constitution of the multitude, and thus, of political forms. our argument will be, first, that this statement is not coherent with the complexity of Spinoza’s work, and secondly, that it constitutes the heart of the Straussian interpretation of Spinoza.
Keywords: Religion; Critique; Imagination; Reason; Rule; Multitude